STUDI MANAJEMEN MATERIAL PADA PROYEK PEMBANGUNAN GEDUNG KULIAH STFK LEDALERO DI KABUPATEN SIKKA - Natalia Lamba Parinding; Oktavianus Jori; Dedi Imanuel Pau (Program Studi Teknik Sipil, 2022)
building contrruction is something fasiltas Building construction is something facilities made _ by man for support various activity activity Public that alone . one _ indicator success something project is with existence good material control in the field . Material control meets accuracy , identification , and accuracy time ,and control all the materials needed in the field . Good material management is system consistent management _ and support on moment procurement and on moment construction .with Thus the activity process development project the will could done by good and fluent without experience obstacle . Development process building STFK Ledalero campus need planning good material management so that the material inventory process does not hampered so that no disturbing profession and could walk with good . As for destination in study is for knowing material needs and application field material management . Study started with count material requirements and material delivery processes , material receipts , material storage in the field . Results from study this on material requirements obtained 55775 pieces stone bricks , cement as much as 229.8 bags , and sand as much as 34.26 m 3 on profession wall 2nd floor while work material needs Portland cement stucco as much as 331.46 zak , dan sand pairs 50.99 m 3 . Application field material management it takes a good time schedule for work development can walk with good .